2005
DOI: 10.1096/fj.04-3403com
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activators promote excitotoxicity‐induced retinal damage

Abstract: Increased levels of extracellular L-glutamate have been suggested to play a role in retinal damage in a number of blinding diseases such as glaucoma and diabetic retinopathy. Although glutamate can cause retinal damage, in part, by hyper-stimulating its receptors ("excitotoxicity"), the down-stream events that lead to retinal damage are poorly understood. In this study, we injected kainic acid (KA), a glutamate receptor agonist that specifically hyper-stimulates non-NMDA-type receptors, into the vitreous humor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
57
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 72 publications
(94 reference statements)
6
57
2
Order By: Relevance
“…We, therefore, considered that the range of the dose of tPA (0.075-7.5 μg) in our study is equivalent to 2.5 to 250 μg in clinical use. We estimated that the dosing range was appropriate because dose dependency in the non-CRVO groups in our study was consistent with the results of previous studies of cats and rabbits [6,12]. In the non-CRVO group, we did not administer the dose of 0.075 μg tPA, because we considered this dose of tPA would not cause retinal toxicity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We, therefore, considered that the range of the dose of tPA (0.075-7.5 μg) in our study is equivalent to 2.5 to 250 μg in clinical use. We estimated that the dosing range was appropriate because dose dependency in the non-CRVO groups in our study was consistent with the results of previous studies of cats and rabbits [6,12]. In the non-CRVO group, we did not administer the dose of 0.075 μg tPA, because we considered this dose of tPA would not cause retinal toxicity.…”
Section: Discussionsupporting
confidence: 71%
“…An excessive amount of intravitreal tPA, however, causes retinal toxicity [6][7][8][9][10][11][12][13][14][15]. Intravitreal injection of commercially available tPA in concentrations equal to or greater than 50 μg/0.1 ml are toxic in cat and rabbit eyes [6][7][8][9][10], and previous studies hypothesized that L-arginine in the vehicle may have toxic effects on the outer retina [11,12]. Patients treated with 100 μg of tPA for submacular hemorrhage had both inferior exudative retinal detachment and retinal pigment epithelium (RPE) hyperpigmentation [13], and a patient treated with two successive intravitreal injections of 50 μg of tPA for submacular hemorrhage had diffuse RPE changes and reduced electroretinogram amplitudes [14].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Sucher et al 7 reported that glutamate acts predominantly by binding to NMDA receptors, which triggers apoptosis by promoting Ca 2þ influx into the cell and consequent activation of the caspase cascade. Mali et al 8 demonstrated that KA-induced retinal damage promotes the upregulation of tissue tPA and the induction of uPA, which resulted in plasminogen activation to plasmin, extracellular matrix degradation, and apoptosis in the RGC layer as well as in the inner and outer nuclear layers. In a parallel study, Kumada et al 29 identified tPA as directly responsible for KA-induced retinal damage independently from cleavage of plasminogen to plasmin.…”
Section: Discussionmentioning
confidence: 99%
“…7 Moreover, via hyperstimulation of the non-NMDA receptors, glutamate upregulates tissue plasminogen activator (tPA) and urokinase plasminogen activator (uPA), which catalyze plasminogen activation to plasmin, leading to degradation of the extracellular matrix and RGC apoptosis. 8 Although the precise role of excitotoxicity in human glaucoma is still a matter of considerable debate, mice that represent various models of NTG continue to serve as a basis for investigating neuroprotective strategies aimed at excitotoxic insults to the CNS. 9 Intraocular injection of excitotoxic agents is commonly used to induce a relatively specific insult to RGCs in the absence of increased IOP in rodents.…”
mentioning
confidence: 99%
“…Glutamate under physiologic conditions is encountered as an excitatory transmitter throughout the whole central nervous system and the inner retina 7,8 . Elevated glutamate levels have been found not only in glaucoma and retinal detachment 5,6 but also in proliferative diabetic retinopathy 9 .…”
Section: Introductionmentioning
confidence: 99%